ICT LITERACY FOR ENGLISH TEACHER IN NUSA PENIDA DISTRICT- BALI - Juniarta, Putu Adi Krisna (Universitas Pendidikan Ganesha, 2017)
The English teacher in Nusa Penida district, Klungkung regency almost applied teacher centered method in teaching and learning process. It was caused by the sources of learning was only from the teacher and book that was used in the class. It made teaching and learning process became monotone and bored. Reflected to that problem, IBM team build relationship with the group of English teacher of Junior High School in Nusa Penida in order to improve competency of the used of ICT as the tool used in teaching and learning activity. The method that was used to train the English teacher was apprentice training by implementing cognitive apprenticeship model. This IBM had been conduted for 8 months and it resulted: (1) the competency of English teacher in operating ICT during teaching and learning proess in the class was improved, (2) the English teacher’s respond that used cognitive apprenticeship model during the training activity were positive. It could be seen from the Englisgh teachers’ enthusiasm during the training activity.Key words: ICT, model cognitive apprenticeship, English Teacher